Pituitary adenylate cyclase activating polypeptide acts against neovascularization in retinal pigment epithelial cells - Fábián Eszter; Reglődi Dóra; Horváth-Opper Gabriella; Opper Balázs; Tóth Gábor; Fazakas Csilla; Végh Attila Gergely; Wilhelm Imola Mária; Krizbai István Adorján (2019)
The purpose of this study was to determine whether pituitary adenylate cyclase activating polypeptide (PACAP) could influence the neovascularization processes in hyperosmotic and oxidative stress in retinal pigment epithelial cells. Hyperosmotic conditions and oxidative stress were induced by 200 mM sucrose and 250 µM hydrogen peroxide (H2 O2 ), respectively. Morphology and elasticity of adult retinal pigment epithelial (ARPE-19) cells were measured by atomic force microscopy, while the investigation of junctional molecules, such as occludin and ZO-1, was carried out using immunofluorescence. For cell viability measurement, the MTT test was used. The effect of PACAP on the key angiogenic factors, such as vascular endothelial growth factor, angiogenin, and endothelin-1, was measured by an angiogenesis array and flow cytometry. Hyperosmotic stress-induced reorganization of the cytoskeleton and impairment of the junctions decreased cell viability and upregulated several angiogenic factors. In oxidative stress, we found that opening of the junctions decreased viability and upregulated the expression of angiogenic factors. PACAP was shown to be protective in both conditions. Retinal pigment epithelium cells play an important role in several diseases, such as diabetic retinopathy and macular edema. Therefore, protecting retinal pigment epithelial (RPE) cells with PACAP could be a novel and potential treatment in these diseases.